Contact Analysis for Beveloid Pinion and Rack Considering Axial Clearance Change - Huang Hongxin; Zhao Xingfu; Wang Zengqiang; Yu Guangbin (Jixie chuandong)
Aiming at the problems that clearance is difficult to modify and operation stability is poor of pinion and rack used in the large machine tool carrier feeding device，the beveloid pinion and rack which can modify clearance axially is proposed.The finite element analysis of the changes of variables such as static transmission error，uniform degree of contact stress，contact force are carried out when considering axial clearance changes.The results show that the influences of axial clearance changes to variables depend on torques directly，the influences when torque is 50 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m or 100 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m from large to small are in the order of uniform degree of contact stress，static transmission error，contact force.The influences when torque is 200 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m or 400 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m from large to small are in the order of static transmission error，uniform degree of contact stress，contact force.